Catholic missions in China: failure to form native clergy. Issue 1 (2nd January 2019) - Mong, Ambrose
ABSTRACT: The success and failure of Christianity in China was tied to the missionaries' ability to accommodate to Chinese culture and the powers that ruled over this vast nation. A number of reasons have been put forward regarding the failure of Christian missions in China. Inability to adapt to native norms, ignorance of Chinese language, association with Western imperialism, rivalries among various religious orders, congregations and missionary societies, and the reluctance to establish a Chinese ecclesiastical hierarchy all contributed to hindering the propagation of the gospel. This paper argues that the main reason for their failure was the refusal of European clergy to hand over the leadership of the church to the Chinese, in spite of Rome's edicts to establish an indigenous ecclesiastical hierarchy. With local clergy in charge, the issue of language and cultural adaptation would have been resolved. Unfortunately, the native clergy were looked down upon by their Western counterparts, who were mostly motivated by national and institutional interests rather than pastoral concern for the local people. The appointment of the first Chinese bishop, Gregorio Lopéz (Luo Wenzao), was more a political move than a pastoral need.